EXPLORATION AND IDENTIFICATION OF INSECTS IN ORNAMENTAL PLANTS IN THE FIELD - Jun Masnia Hia; Octanina Sari Br Sijabat; Ahmad Nadhira (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Flowering ornamental plants have an important role as an aesthetic element as well as a microhabitat for various types of insects. The presence of insects in ornamental plants can have a positive impact as pollinators, predators, parasitoids, and decomposers, but some others have the potential to be detrimental because they act as pests. This study aims to explore and identify the types of insects found in various flowering ornamental plants and classify their roles as beneficial or detrimental insects. The study uses an exploratory descriptive method with purposive sampling techniques on 11 types of flowering ornamental plants in the field. Insect sampling was carried out using the sweep net method of 10 swings on each observation plot, then the insects caught were identified based on morphological characteristics. The data was analyzed in a quantitative descriptive manner through the calculation of density, frequency, and Shannon-Wiener diversity index. The results showed that flowering ornamental plants are a place for various types of insects with different compositions and abundance in each type of plant. The insect diversity index value is generally in the medium category, with variations between morning and evening observations. The insects found consist of potentially beneficial groups, such as pollinators and predators, as well as detrimental groups, such as aphids, whiteflies, thrips, and plant fluid-sucking insects. This study shows that the identification of insects in ornamental plants is important as the basis for sustainable and environmentally friendly management of ornamental plants.